2013
DOI: 10.4236/wjcs.2013.35027
|View full text |Cite
|
Sign up to set email alerts
|

Source, Triggers and Clinical Implications of Hyperlactemia in Patients Undergoing Mitral Valve Surgery Using Custodiol Cardioplegia

Abstract: Background: Postoperative blood hyperlactaemia is an indicator of organ anaerobic metabolism and is associated with morbidity after cardiac surgery. This prospective study aims to explore the source, triggers and clinical implications for hyperlactaemia in patients undergoing mitral valve surgery using Custodiol cardioplegia. Methods: Twenty consecutive elective patients undergoing open-heart surgery for mitral valve repair/replacement using Custodiol (based on Bretschneider's HTK-solution) cardioplegia were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Second, cardioplegia and hemodilution of crystalloid pump primers can reduce blood viscosity and overall vascular resistance. On the other hand, some findings seem to suggest that Custodiol ® cardioplegia could be associated with the release of blood lactate immediately after aortic clamp release and with the appearance of VS in the postoperative period ( 9 ). Larger studies are required to determine the risks and benefits balance of Custodiol ® in patients undergoing mitral valve surgery and in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, cardioplegia and hemodilution of crystalloid pump primers can reduce blood viscosity and overall vascular resistance. On the other hand, some findings seem to suggest that Custodiol ® cardioplegia could be associated with the release of blood lactate immediately after aortic clamp release and with the appearance of VS in the postoperative period ( 9 ). Larger studies are required to determine the risks and benefits balance of Custodiol ® in patients undergoing mitral valve surgery and in pregnant patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ascione et al (21) found that, relative to preoperative values, a time-dependent rise in blood lactate was noticed right after the removal of the aortic cross-clamp and continued to be high at 48 hours later.…”
Section: Figure (2) Intraoperative Map (Mmhg) Assessment Of the Studi...mentioning
confidence: 96%